Uma análise comparativa entre os sinais de pontuação do português x o parâmetro expressão facial e corporal em uma fábula traduzida para Libras - SILVA, David Ferreira da (2022)
In the last decades, discussions and academic studies about the bilingual teaching to deaf people has been gaining more and more space in the scientific researches. However, the deaf students still have difficult in the comprehension and learning of some aspects in the written Portuguese – considered as L2 of this community in Brazil – as the case of punctual signs in Portuguese. This work has as aim to verify if the use of the genre Fable translated to Libras may contribute to the teaching of graphic signs of Portuguese punctuation in the written mode of deaf students. For this, it was necessary to: understand the functioning of punctual signs of Portuguese written and the Parameter Facial and Body Expression in Libras; identify possible similarities and differences in punctuation between languages that are of different modalities; to analyze which graphical punctual signs from Portuguese were translated to the fable analyzed in Libras. And finally, to identify the contributions that the fable genre brings to the teaching of Portuguese in the written mode for deaf people. As theoretical contribution on this research, it has used studies of Pagura (2003), Santiago and Lacerda (2016), Araujo and Carvalho (2017); Jakobson (1969); Segala and Quadros (2015), among others, about the interlingual translation between LIBRAS and Portuguese. Quadros (1997); Carvalho (2017), Soares (1998) and Pereira (2009) to the comprehension of the purpose of bilingual teaching to deaf students. Marcuschi (2008); Bagno (2006); Silva (2017); Santos (2016) about the text genre Fable. Soares (2017) and Bechara (2019) about the punctual signs of Portuguese language, and Brito (1997) to the Parameter of Facial and Body expression of LIBRAS. This is a qualitative research with comparative analysis between the operation of punctuation signs in Portuguese and its translation to Libras through the parameter facial and body expression on the fable “And who said that…that I do not speak?” by the writer Uendy Feitosa. This fable which was written in Portuguese and translated to Libras, registered in video available on Youtube. The research showed that there is relation between the punctual signs in Portuguese and the Parameter Facial and Body expressions of Libras, in addition, it has showed that the use of a text genre in mother language of deaf people can facilitate their understanding and learning of written Portuguese.